Cartographies des marges : intersectionnalité, politique de l'identité et violences contre les femmes de couleur - Crenshaw, Kimberlé W. (Cahiers du Genre, 2005)
Les discours féministes et antiracistes contemporains n’ont pas su repérer les points d’intersection du racisme et du patriarcat. Face à ces difficultés, cet article propose une approche originale : l’intersectionnalité. La première partie traite de l’intersectionnalité structurelle — de la manière dont le positionnement des femmes de couleur, à l’intersection de la race et du genre, rend leur expérience concrète de la violence conjugale, du viol et des mesures pour y remédier qualitativement différente de celle des femmes blanches. La seconde partie porte sur l’intersectionnalité politique : notamment la marginalisation de la question de la violence contre les femmes de couleur induite par les politiques féministes et antiracistes. Enfin, l’article conclut par l’examen des conséquences de l’approche intersectionnelle dans le champ plus large de la politique de l’identité contemporaine. [*]
https://www-cairn-info.proxy.bibliotheques.uqam.ca/revue-cahiers-du-genre-2005-2-page-51.htm
Keywords: 1900-1999; afro-féminisme; amériques; approches et analyses; com5170; cours; cycles supérieurs; fem1000; fem3300; fem7000; féminismes noirs; har4600; har4610; incontournable; intersectionnalité; lit2815; lit3220; lit3495; patriarcat; phi4336; pol4022; pol4102; pol4105; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques; violences; violences contre les femmes*; états-unis

Black sexual politics: African Americans, gender, and the new racism - Hill Collins, Patricia (Routledge, 2005)
To a large extent, scholarship on black politics often focuses primarily on institutions, rule of law, processes, political actors, and citizens but with very little attention to issues of gender and sexuality. In contrast, the principal aim of this book is to explore what the author sees as the inextricable links between racism and gender. The basic thesis of this well-written, important, and provocative book is that the fight against racism, especially the “new racism,” can never be won without first challenging sexism, which simultaneously oppresses African-American men and women.
Section: ix, 374 p. ; 23 cm
Keywords: afro-féminisme; amériques; approches et analyses; corps; cours; discipline; féminisme afroaméricain; féminismes noirs; intersectionnalité; premier cycle; racisme; ressource en ligne; régions géographiques; science politique; science politique et droit; sciences humaines; sex2283; sexisme; sexualité; sociologie; systèmes d'oppressions; thématiques; théorie critique de la race; violences; états-unis

Attitudes Toward Victims of Rape: Effects of Gender, Race, Religion, and Social Class - Nagel, Barbara; Matsuo, Hisako; McIntyre, Kevin P.; Morrison, Nancy (Journal of Interpersonal Violence, 2005)
Although previous literature focusing on perceptions of victims of rape has examined how gender, race, and culture influence the attitudes one holds toward victims, these studies have yielded mixed results. This study compared perceptions of victims of rape across a wide range of ages, educational backgrounds, religions, and income levels, while focusing on gender and racial differences. Results indicate (N = 220) that victims of rape are generally viewed more sympathetically by females than by males and by Whites than by African Americans. However, the effect of race disappears when socioeconomic variables are controlled, suggesting a more complex relationship. Also, a hierarchical regression indicates that age, sex, education, and income are significant predictors of attitudes toward victims. This study builds on existing research that examines such attitudes from a cultural perspective and extends this literature by examining the interactive effects of several demographic variables within a community sample.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; anthropologie; approches et analyses; corps; cours; discipline; intersectionnalité; premier cycle; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sex2283; thématiques; viol; violences; états-unis

Native american feminism, sovereignty, and social change - Smith, Andrea (Feminist Studies, 2005)
Smith argues that any serious conceptualization of Native American women as feminist activists demands a rejection of the reductive dichotomy of feminist versus nonfeminist. For her, one must first understand the diversity of opinions about feminist activism that exists among Native women and how they have uniquely conceived both their role as activists and their theoretical frameworks. In addition, for many Native women the traditional assumption that a feminist's first aim is to combat sexism is inadequate for dealing with the equally important problem of Native American sovereignty.
Number: 1 http://www.feministstudies.org/home.html
Keywords: 2000 à aujourd'hui; 2000-2009; OFDIG; approches et analyses; féminisme autochtone; intersectionnalité; périodes historiques; ressource en ligne; thématiques; violences; violences coloniales; violences contre les femmes*; violences sexuelles

Domestic violence at the intersections of race, class, and gender: challenges and contributions to understanding violence against marginalized women in diverse communities - Sokoloff, Natalie J; Dupont, Ida (Violence against women, 2005)
This article provides a comprehensive review of the emerging domestic violence literature using a race, class, gender, sexual orientation intersectional analysis and structural framework fostered by women of color and their allies to understand the experiences and contexts of domestic violence for marginalized women in U.S. society. The first half of the article lays out a series of challenges that an intersectional analysis grounded in a structural framework provides for understanding the role of culture in domestic violence. The second half of the article points to major contributions of such an approach to feminist methods and practices in working with battered women on the margins of society.
Keywords: 2000 à aujourd'hui; 2000-2009; afro-féminisme; amériques; approches et analyses; care; corps; cours; criminologie; discipline; féminisme afroaméricain; intersectionnalité; premier cycle; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sex2283; sociologie; thématiques; violences; états-unis